Regulation of TIA-1 Condensates: Zn2+ and RGG Motifs Promote Nucleic Acid Driven LLPS and Inhibit Irreversible Aggregation - West, Danella L.; Loughlin, Fionna E.; Rivero-Rodríguez, Francisco; Vankadari, Naveen; Velázquez-Cruz, Alejandro; Corrales-Guerrero, Laura; Díaz-Moreno, Irene; Wilce, Jacqueline A. (Frontiers in Molecular Biosciences, 2022)
Stress granules are non-membrane bound RNA-protein granules essential for survival during acute cellular stress. TIA-1 is a key protein in the formation of stress granules that undergoes liquid-liquid phase separation by association with specific RNAs and protein-protein interactions. However, the fundamental properties of the TIA-1 protein that enable phase-separation also render TIA-1 susceptible to the formation of irreversible fibrillar aggregates. Despite this, within physiological stress granules, TIA-1 is not present as fibrils, pointing to additional factors within the cell that prevent TIA-1 aggregation. Here we show that heterotypic interactions with stress granule co-factors Zn2+ and RGG-rich regions from FUS each act together with nucleic acid to induce the liquid-liquid phase separation of TIA-1. In contrast, these co-factors do not enhance nucleic acid induced fibril formation of TIA-1, but rather robustly inhibit the process. NMR titration experiments revealed specific interactions between Zn2+ and H94 and H96 in RRM2 of TIA-1. Strikingly, this interaction promotes multimerization of TIA-1 independently of the prion-like domain. Thus, through different molecular mechanisms, these stress granule co-factors promote TIA-1 liquid-liquid phase separation and suppress fibrillar aggregates, potentially contributing to the dynamic nature of stress granules and the cellular protection that they provide.